MENULIS RAPI DAN SESUAI EYD SEBAGAI UPAYA PENGUATAN LITERASI SISWA KELAS V SEKOLAH DASAR - Muhammad Faiz; Firdaus, Ahmad; Cindy Desiana; Odien Rosidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The skill of writing neatly and according to the Refined Spelling (EYD) is an important aspect in strengthening student literacy, especially at the elementary school level. This study aims to improve the habit of writing neatly and according to EYD in grade V students of SDN 11 Serang through a habituation-based approach. The method used was Classroom Action Research (PTK) with the Kemmis and McTaggart model involving three cycles. The results showed significant improvement in two main aspects: the neatness of students' writing increased from 45% in the first cycle to 85% in the third cycle, while the compliance with EYD increased from 40% to 90%. These improvements were achieved through structured practice, constructive feedback, and intensive mentoring by teachers. The findings support Vygotsky's theory on the importance of active interaction in learning and underline the role of habituation in the acquisition of writing skills. This study recommends the sustainable implementation of habituation-based learning strategies to support the strengthening of students' literacy.